Associations between age-related hearing loss, cognitive decline, and depression in Chinese centenarians and oldest-old adults. (March 2022) - Feng, Long; Wu, Di; Lin, Jieqiong; Li, Yulong; Zhao, Yali; Zhang, Pei; Yao, Yao; Fu, Shihui
Objective: Age-related hearing loss (ARHL) and age-related cognitive decline (ARCD) are leading causes of disability in older adults. ARHL may increase ARCD risk and cause depression development. This study aimed to explore the associations of ARHL with ARCD and depression in Chinese centenarians and oldest-old adults. Methods: A household survey was conducted on 859 centenarians and oldest-old adults residing in 16 cities and counties in China. Basic information was collected using interview questionnaires, physical examinations, and blood tests conducted by systematically trained local doctors and nurses. Results: In total, 501 (58.3%), 649 (75.6%), and 211 (24.6%) participants had ARHL, ARCD, and depression, respectively. The prevalence of ARCD and depression was significantly higher in participants with ARHL than in those without ARHL (all p < 0.05). Participants with ARHL had significantly lower Mini-Mental State Examination (MMSE) scores indicative of more cognitive decline, and significantly higher 15-item version of the Geriatric Depression Scale (GDS-15) scores suggesting greater levels of depression, than those without ARHL (all p < 0.05). Multivariate logistic regression analyses (Stepwise) indicated that ARHL was significantly and positively associated with ARCD [odds ratio (OR): 1.594, 95% confidence interval (CI): 1.132, 2.245] and depression (OR: 1.623, 95% CI: 1.139, 2.314; all p < 0.05). Multivariate linear regression analyses (Stepwise) indicated that ARHL was significantly and inversely associated with MMSE scores ( B : −2.520, 95% CI: −3.356, −1.684) and significantly and positively associated with GDS-15 scores ( B : 0.713, 95% CI: 0.328, 1.098; all p < 0.05). Conclusion: ARHL is independently associated with ARCD and depression in Chinese centenarians and oldest-old adults.